Three-year outcomes of a fracture liaison service model at a university-based tertiary care hospital in Thailand - Chotiyarnwong P. (2023)
Summary: Fragility hip fracture (FHF) is a serious complication of osteoporosis. A fracture liaison service (FLS) is crucial in preventing FHF. Our retrospective data of 489 patients with FHF and 3-year follow-ups demonstrated that the FLS improved functional outcomes. Our study’s mortality rates were lower than in other published series. Purpose: This study assessed the 3-year outcomes after fragility hip fracture (FHF) treatment by a multidisciplinary team from the Siriraj Fracture Liaison Service (Si–FLS). The review investigated the administration rates of anti-osteoporosis medication, refracture, and mortality; activities of daily living; mobility; and health-related quality of life. Methods: A retrospective review was performed of the records of Si-FLS patients given FHF treatment between June 2016 and October 2018. The outcomes were evaluated at 3 time points: before discharge, and 1 and 3 years after treatment. Results: The study enrolled 489 patients (average age, 78). The mortality and refracture rates at 1 year after hip fracture were 13.9% and 1.6%, respectively. At the 3-year follow-up, both rates were higher (20.4% and 5.7%, respectively). The Barthel Index and EuroQoL Visual Analogue Scale had risen to a plateau at the 1-year follow-up and remained stable to the 3-year follow-up. One year after treatment, approximately 60% of the patients could ambulate outdoors, and the proportion remained steady until the 3-year follow-up. There was no difference in the 1- and 3-year follow-up anti-osteoporosis medication administration rates (approximately 40%). Conclusions: This study confirms the benefits of having a multidisciplinary FLS care team to manage older people with FHF. An FLS improves the care of patients with FHF and the social support of caregivers and relatives. The FLS maintained the functional outcomes of the patients through 3 years of postfracture treatment.